2021
DOI: 10.2967/jnmt.121.262627
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Patient Experience Between a 360° γ-Camera and a Conventional Dual-Head γ-Camera

Abstract: Our aim was to explore whether the 360 g-camera design of the Veriton-CT scanner adversely affects the rate of scan noncompletion due to claustrophobia or other patient experience factors, when compared with a standard dual-head Discovery NM/CT 670 g-camera. Methods: This was a single-center prospective study of all nuclear medicine studies on either of the 2 g-cameras. It was recorded whether the patient completed the scan as protocoled or, because of claustrophobia, had a shortened scan or no scan. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Up to now, two major devices rely on 3D-ring CZT design: Veriton SPECT (Spectrum Dynamics Medical) and StarGuide SPECT (GE Healthcare). A recent study using Veriton SPECT found that these new cameras are reliable and that there is no change in the subjective patient experience ( 14 ). Regarding the physical performances, a recent study demonstrated that the Veriton CZT camera has superior sensitivity, higher energy resolution, and better image contrast than the conventional SPECT camera, whereas spatial resolution remains similar ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, two major devices rely on 3D-ring CZT design: Veriton SPECT (Spectrum Dynamics Medical) and StarGuide SPECT (GE Healthcare). A recent study using Veriton SPECT found that these new cameras are reliable and that there is no change in the subjective patient experience ( 14 ). Regarding the physical performances, a recent study demonstrated that the Veriton CZT camera has superior sensitivity, higher energy resolution, and better image contrast than the conventional SPECT camera, whereas spatial resolution remains similar ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Time reduction will be beneficial, as examination failure is often caused by patient's inability to lie down for prolonged period due to dyspnea. 3D-ring CZT-SPECT are well accepted by patients,10 and shorter acquisitions will ease clinical workflow. There is growing interest in lung procedures,11 with new potential indications 12,13.…”
mentioning
confidence: 99%